Unveiling Portuguese governmental libraries trends and challenges: confluence of futures studies, action research and stakeholder analysis - Pinto, Leonor Gaspar; Ochôa, Paula; Barata, Paulo J. S.; Galvão, Rosa Maria; Batalha, Vera (Qualitative and Quantitative Methods in Libraries; Vol 5 No 1 (2016): March 2016 Issue, 2017)
In March 2016, the Directorate General for the Qualification of Public Workers (INA) created an Informal Working Group on Central Public Administration Libraries – Thinking the Future (GIBACE) whose mandate was to develop a strategic guidance document for this library sector. The purpose of this paper is to discuss the methodological approaches used in this process, namely the confluence of future studies, action learning and stakeholders’ analysis, integrating different practices (academy, experts, and organizations) in a participatory action research to think and create shared futures for Central Public Administration Libraries (CPALs). After presenting the methodological approaches, particular attention is given to the outputs generated by the main phases of the action research process: (1) experts’ vision(s) of future; and (2) stakeholder analysis, participation and (co)construction of CPALs´ shared futures. Finally, GIBACE’s recommendations for action are presented, as well as some final remarks concerning the opportunities for research and practice in the Library and Information Science arena.